Nanoparticles and Immune Cells - Mitarotonda, Romina; Giorgi, Exequiel; Desimone, Martín F.; De Marzi, Mauricio C. (Current Pharmaceutical Design, 2019)
Nanoparticles have gained ground in several fields. However, it is important to consider their potentially hazardous effects on humans, flora, and fauna. Human exposure to nanomaterials can occur unintentionally in daily life or in industrial settings, and the continuous exposure of the biological components (cells, receptors, proteins, etc.) of the immune system to these particles can trigger an unwanted immune response (activation or suppression). Here, we present different studies that have been carried out to evaluate the response of immune cells in the presence of nanoparticles and their possible applications in the biomedical field.
Keywords: receptors